2001
DOI: 10.1021/jp012355q
|View full text |Cite
|
Sign up to set email alerts
|

Size Distribution of Gel and Fluid Clusters in DMPC/DSPC Lipid Bilayers. A Monte Carlo Simulation Study

Abstract: Proteins and lipid components are organized into domains in many biological membranes. With different experimental techniques vastly different cluster sizes have been measured in an equimolar mixture of a DMPC/ DSPC two-component lipid bilayer: very small ones in the nanometer range and very large ones of size comparable with the size of the bilayer. In this paper the lateral distribution of gel and fluid lipid molecules in a DMPC/DSPC bilayer is simulated by using a two-state, Ising type model with the applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 39 publications
3
16
0
Order By: Relevance
“…The analysis of the bilayer energy distribution function revealed that the gel-fluid transition is a continuous transition through equilibrium states for DMPC, DSPC, and DMPC/DSPC mixtures; i.e., the system is above the critical point. The same model successfully predicted the excess heat capacity curves and the FRAP threshold temperatures at different mole fractions, the most frequent center-to-center distance between DSPC clusters at different temperatures, the fractal dimensions of the gel clusters, and the upper bound for the size of the small, nonpercolated gel clusters, in good agreement with the respective experimental data (Sugar and Biltonen, 2000;Michonova-Alexova and Sugar, 2001;Sugar et al, 2001). Recently, the geometrical properties of the gel and fluid clusters, such as cluster perimeter, cluster size, number of arms along the cluster perimeter, and number and size of inner islands in a host cluster were characterized in an equimolar mixture of DMPC/DSPC (Sugar et al, 2001).…”
Section: Introductionsupporting
confidence: 67%
“…The analysis of the bilayer energy distribution function revealed that the gel-fluid transition is a continuous transition through equilibrium states for DMPC, DSPC, and DMPC/DSPC mixtures; i.e., the system is above the critical point. The same model successfully predicted the excess heat capacity curves and the FRAP threshold temperatures at different mole fractions, the most frequent center-to-center distance between DSPC clusters at different temperatures, the fractal dimensions of the gel clusters, and the upper bound for the size of the small, nonpercolated gel clusters, in good agreement with the respective experimental data (Sugar and Biltonen, 2000;Michonova-Alexova and Sugar, 2001;Sugar et al, 2001). Recently, the geometrical properties of the gel and fluid clusters, such as cluster perimeter, cluster size, number of arms along the cluster perimeter, and number and size of inner islands in a host cluster were characterized in an equimolar mixture of DMPC/DSPC (Sugar et al, 2001).…”
Section: Introductionsupporting
confidence: 67%
“…the calculated, bimodal distribution of the cluster size (see above), and more than one large cluster can be observed if the lateral distribution of the lipid molecules in the giant vesicle did not attain the equilibrium (Michonova-Alexova and Sugar, 2001). According to our experience one can accelerate the attainment of the equilibrium distribution by means of freezing and thawing cycles (Liu et al, 1997).…”
Section: The Large Clustermentioning
confidence: 95%
“…Computer simulation, in particular molecular dynamics (MD), provides an important contribution to these investigations as an atomistic-precision tool. 8,18,[20][21][22][23][24][25] MD simulations of model bilayers have provided comprehensive insights into structure and function of these fascinating systems. In turn, the area per lipid (APL) of a bilayer provides important information about a bilayer or a membrane, because of its high sensitivity to hydrophilic attraction between head groups and hydrophobic repulsion between non-polar hydrocarbon tails.…”
Section: Introductionmentioning
confidence: 99%